Language Change, New Millennium, and the Watershed in the Use of English - Leotta, Paola Clara; Dolidze, Tamari (European Scientific Journal, ESJ, 2022)
We all agree that language, like any living being, undergoes constant change and evolution to adapt to the needs of its users. Therefore, the English Language being a Lingua Franca is not an exception, and it keeps pace more than other languages in the world with cutting edge developments in all areas of human life with its primary function of effective communication in professional as well as ordinary real-life situations. The development of English as an International Language has become more noticeable since the beginning of globalization. Furthermore, it leads to the definition of Global English(es) and is even more vivid after digitalization in which its significant role and existential function are now unquestionable. Moreover, it is the best communication tool for global citizens, individuals equipped with 21st century skills uniting under one common goal of making the world a better place to live via sharing and exchanging knowledge and expertise, as well as collaborating and cooperating more than ever before, using this powerful weapon connecting us all - English. With this thematic literature review, based on synchronic and diachronic linguistics, the two authors reconstruct and highlight expeditious changes and turning points undergone by the English Language, especially during the COVID-19 pandemic. In the conclusion, a summary of the key findings taken from the literature were given, and their significance were emphasised, as many changes in vocabulary are in order (abbreviations, simultaneous conversations, new uses, new structures, popularised health communication), especially in how they reflect a new language need to express the dynamism of current global challenges.